2018
DOI: 10.1051/matecconf/201825002003
|View full text |Cite
|
Sign up to set email alerts
|

Engineering properties of bitumen modified with bio-oil

Abstract: The current high price of crude oils for bitumen production has led to various studies on the most economical way in replacing or reducing the amount of virgin bitumen as a binder in road pavement while increasing their pavement performance. The aim of this study is to investigate the effect of using bio-oil, particularly waste cooking oil, (WCO) on the engineering properties of bitumen. Both physical and rheological properties of the original bitumen and WCO modified bitumen were measured using penetration, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Due to this, the aged binder already loses the impurity and particles during the service life of asphalt pavement. Also, the loss on heating values in the binder with 25% and 40% of RAPB content slightly lower compared to the other binders, which was consistent with previous research [44]. The binders with 25% and 40% of RAPB content incorporating a combination of WFO and CR have comparable result values to the virgin bitumen.…”
Section: Loss Of Heatingsupporting
confidence: 90%
“…Due to this, the aged binder already loses the impurity and particles during the service life of asphalt pavement. Also, the loss on heating values in the binder with 25% and 40% of RAPB content slightly lower compared to the other binders, which was consistent with previous research [44]. The binders with 25% and 40% of RAPB content incorporating a combination of WFO and CR have comparable result values to the virgin bitumen.…”
Section: Loss Of Heatingsupporting
confidence: 90%
“…The use of bio-asphalt in asphalt mixtures is currently considered as one of the main alternatives for reducing bitumen consumption, which has environmental, economic, and health benefits [1][2][3][4][5][6][7][8][9][10]. Some of these bio-binders that studied and showed promising results include sugar cane molasses [11][12][13][14], beet molasses [15], swine manure [1,16,17], waste cooking oil [6,9,[18][19][20], and wood waste [21,22]. However, the studies indicated that bio-asphalts are moisture susceptible because moisture can have serious effects on the durability of hot-mix asphalt HMA pavements.…”
Section: Introductionmentioning
confidence: 99%
“…When the binder is softer, the lesser the consistency, and the higher the penetration. As shown in Table 5 , test results by He et al [ 60 ], Li et al [ 61 ] and Rasman et al [ 62 ] showed the difference in penetration between base binders and bio-asphalts. As the bio-oil content increased, the penetration of asphalt binders enhanced gradually.…”
Section: Properties Assessment Of Bio-oil Modified Asphalt Bindersmentioning
confidence: 96%
“…As the bio-oil content increased, the penetration of asphalt binders enhanced gradually. Moreover, in order to satisfy the penetration grade of 80/100 for asphalt, waste cooking oil (WCO) could be used with a dosage of only 2% at most [ 62 ]. However, for the source of palm kernel oil polyol, 20% bio-oil promoted the enhancement of asphalt binder penetration, whereas a higher content of 40% and 60% bio-oil decreased its penetration.…”
Section: Properties Assessment Of Bio-oil Modified Asphalt Bindersmentioning
confidence: 99%